Reconhecimento judicial da união entre pessoas do mesmo sexo como união estável e entidade familiar: criação do direito ou efetivação da Constituição? - Azevedo, Silvagner Andrade de (2011)
The research investigates the legitimacy of judicial recognition of unions between same-sex people, thus characterized as family entities. The hypothesis is that this recognition does not constitute judicial creation of law, implying an illegitimate decision from the perspective of separation of powers, but stem from the constitutional pre-existing demand placed on the assessment of the judiciary and the enforcement of fundamental rights of minorities. Given the preliminary finding that the alleged creation is affected by the lack of consensus about what is law, examines two theoretical conceptions of law: legal positivism of H.L.A. Hart and law as integrity of Ronald Dworkin. Notes that the two concepts investigated respond differently to the question posed. In light of the legal theory of Ronald Dworkin, the theoretical framework of this research, the working hypothesis is partially ratified, it can be inferred that the judicial recognition of unions between same sex people does not result necessarily creation of law. Examines, in sequence, this recognition stems from the application of constitutional norms and the enforcement of fundamental rights of minorities, due to the precepts of modern constitutionalism, confirming the hypothesis in its entirety. Finally, consider the analysis, in the theoretical and legal perspective presented, of cases involving the legal recognition of unions between same-sex people, who have been or are about to be judged by the higher instance of national judiciary, specifically by Superior Electoral Court, which ruled in the 2004 the Election Special Appeal No. 24,564, and the Supreme Court, which is about to judge the ADPF No. 132.